Determinants of the Fiscal Support of Governments in Response to the COVID-19 Pandemic - Li, Sheng-Kun; Liang, Xueping (Frontiers in Public Health, 2021)
Fiscal support measures have different implications for public finances in the short term and beyond the COVID-19 pandemic. For this purpose, this paper examines the determinants of governments' fiscal support in response to the COVID-19 pandemic. The empirical analysis is based on the cross-sectional data estimations from 129 developed- and developing countries. The estimation results indicate that a higher level of uncertainty related to the COVID-19 (measured by the World Pandemic Uncertainty Indices) is positively related to the fiscal support. Besides, countries with a higher total population and population over 65-years and older provide higher fiscal support. These results are valid to consider the developed countries separately. Policy implications for public finances during the COVID-19 pandemic are also discussed.